Android Based Multimedia for Teaching Science in Junior High School - Ramli, Irwan; Nurasia, Nurasia; Khaerati, Khaerati (Universitas Muhammadiyah Makassar, 2025)
The COVID-19 pandemic has profoundly transformed global education, necessitating adaptive learning strategies to overcome the challenges of remote science instruction. This study aimed to develop and evaluate Android-based interactive multimedia using Adobe Flash CS for science learning, particularly human excretory system material, at Sukamaju State Junior High School 1. The research employed a Research and Development (R&D) approach based on the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. The study involved 27 students from class VIII, selected through simple random sampling. Data were collected using expert validation sheets, teacher and student response questionnaires, and student learning outcomes assessments. The results indicated that the developed multimedia met all quality standards: media expert validation (98.5%), material validation (97%), language validation (86%), and video content validation (92%), all categorized as “very valid.” In terms of practicality, teacher and student responses yielded scores of 98% and 84.2%, respectively, indicating high practicality. Regarding effectiveness, student learning outcomes averaged 87.23%, and class completeness reached 81.4%, both falling into the “very effective” category. These findings demonstrate that Android-based science multimedia significantly enhances student engagement and learning outcomes by offering visually rich, interactive, and flexible educational content. The multimedia enables autonomous learning and supports teachers in delivering effective science instruction. Future research is recommended to broaden the content coverage across subjects and to develop applications compatible with online platforms for wider accessibility.